The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/aic.16110
|View full text |Cite
|
Sign up to set email alerts
|

Supra‐monolayer coverages on small metal clusters and their effects on H2 chemisorption particle size estimates

Abstract: H 2 chemisorption measurements are used to estimate the size of supported metal particles, often using a hydrogen-tosurface-metal stoichiometry of unity. This technique is most useful for small particles whose sizes are difficult to estimate through electron microscopy or X-ray diffraction. Undercoordinated metal atoms at the edges and corners of particles, however, make up large fractions of small metal clusters, and can accommodate multiple hydrogen atoms leading to coverages which exceed 1 ML (supra-monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 79 publications
8
56
0
Order By: Relevance
“…These characterization data indicate that single-crystal extended surfaces, large nanoparticles, and atomically dispersed Rh each have distinct adsorbate coverages and binding modes, but these complexities have seldom been considered in the development and use of DFT models of transition-metal catalysts. Recently, adsorptions on nanoparticle models have been studied with DFT and contrasted to single-crystal surfaces and have shown that nanoparticles can have higher coverages than surfaces, including supramonolayer coverages. For example, our prior work shows that H*-covered 201-atom Ir and Pt particles saturate at 1.59 and 1.30 ML, respectively, during H 2 chemisorption, which is typically used to probe the size of metal nanoparticles. Similarly, DFT calculations indicate that CO* saturates Ru 201 particles at > 1 ML but Ru(0001) surfaces at 0.75 ML ,, and that S* saturates Ru, Re, and Pt nanoparticles at higher coverages than their corresponding (111) or (0001) surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…These characterization data indicate that single-crystal extended surfaces, large nanoparticles, and atomically dispersed Rh each have distinct adsorbate coverages and binding modes, but these complexities have seldom been considered in the development and use of DFT models of transition-metal catalysts. Recently, adsorptions on nanoparticle models have been studied with DFT and contrasted to single-crystal surfaces and have shown that nanoparticles can have higher coverages than surfaces, including supramonolayer coverages. For example, our prior work shows that H*-covered 201-atom Ir and Pt particles saturate at 1.59 and 1.30 ML, respectively, during H 2 chemisorption, which is typically used to probe the size of metal nanoparticles. Similarly, DFT calculations indicate that CO* saturates Ru 201 particles at > 1 ML but Ru(0001) surfaces at 0.75 ML ,, and that S* saturates Ru, Re, and Pt nanoparticles at higher coverages than their corresponding (111) or (0001) surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the use of a stoichiometric factor of adsorbed hydrogen/surface metal of 1. Almithn and Hibbitts calculated the stoichiometric factors for hydrogen adsorption for Ir and Pt as 1.84 to 3.63, respectively, for mean particle sizes of 2.4 to 0.8 nm [33]. They showed in their density-functional theory (DFT) calculations that bulk H* species are not to be expected for those metals, but that under-saturated atoms, in particular, bind to more than one hydrogen atom each.…”
Section: H 2 Chemisorption Resultsmentioning
confidence: 99%
“…Siddiki explained the activity trends of the transition metals in terms of the calculated adsorption energy for hydrogen in a µ 3 -capping position on the most stable metal surface. This does not take into account the size effects of the metal particles, as adsorption energies change with the binding position and particle size [33]. By plotting the TOF against the d-band center of the bulk metal, we also ignored the influence of particle size.…”
Section: Catalytic Experimentsmentioning
confidence: 99%
“…These tools were used to examine how H2 chemisorbs (as H*) on Pt and Ir nanoparticles by calculating ensembles of H2 chemisorption at sub-to supramonolayer coverages. 19 Thousands of structures can be programmatically generated without any manual setup of structures, greatly reducing user time and error. Surface reactions, once converged for one catalyst model, can then be modified by adding co-adsorbates, as just described, to examine coverage effects.…”
Section: Structure Generation and Manipulationmentioning
confidence: 99%